The Effect of Exhibitors’ Brand Equity on Visitors’ Purchase Intention: Moderating Role of 3D Experiential Marketing - Hung, Chao-Chih; ., Wen-Long Zhuang (Information Management and Business Review, 2015)
This study explores the effect of exhibitors’ brand equity on visitors’ purchase intention, as well as the moderating effect of visitors’ 3D experiential marketing on the above relationship. This study examined the visitors to a Taiwanese company’s exhibition booth at a famous India international mechanical fair. One hundred and fifty questionnaires were distributed and 103 valid surveys were returned, indicating a response rate of 68.67%. Empirical results indicated that exhibitors’ brand equity and visitors’ purchase intention are significantly and positively related; the interactive effect of visitors’ think experience and exhibitors’ brand equity is significantly related to visitors’ purchase intention.